Clinicopathologic characteristics of mixed epithelial/mesenchymal metaplastic breast carcinoma (carcinosarcoma): a meta-analysis of Chinese patients - Dequan Xu; Limin Hou (Polish Journal of Pathology, 2019)
Breast carcinosarcoma is a rare and aggressive subtype of metaplastic breast cancer. Data focusing on breast carcinosarcoma is limited. The purposes of this study are to describe the clinicopathological features of breast carcinosarcoma and to evaluate post-surgical outcomes. Material and methods: All case reports about breast carcinosarcoma in China were collected from eligible papers published in Chinese core periodicals between 1990 and 2015 with key words of breast carcinosarcoma, breast cancer, carcinosarcoma, or metaplastic carcinoma. The survival rates, clinical behaviour, and pathological characteristics were analysed. Results: The mean age of the cohort of 215 patients was 53 years (range, 25-82 years). The tumour size ranged from 2.5 cm to 18 cm. The incidence of pathologically confirmed lymph node metastases was 30.81%. The epithelial component in a tumour may be composed of invasive ductal carcinoma (84.21%), squamous cell carcinoma (7.89%), lipid-rich carcinoma (6.58%), or adenocarcinoma (1.31%). Mesenchymal components may contain different elements ranging from fibrosarcoma (63.16%) to chondrosarcoma (19.73%), osteosarcoma (9.21%), liposarcoma (3.95%), or leiomyosarcoma (3.95%). The five-year survival of the breast carcinosarcoma in 149 patients is 62.6% (CI: 54.9%~0.703%). Conclusions: Breast carcinosarcoma is a rare subtype of metaplastic breast cancer. It is characterised by large tumour size, higher rates of axillary nodal involvement, higher rates of both local and distant recurrence, and is difficult to diagnose with preoperative core needle biopsies. Adjuvant treatment after surgical operation may improve the five-year OS of patients with breast carcinosarcoma.